2014
DOI: 10.1002/asia.201402367
|View full text |Cite
|
Sign up to set email alerts
|

1,4‐Dihydropyrrolo[3,2‐b]pyrrole and Its π‐Expanded Analogues

Abstract: Various approaches to the synthesis of 1,4-dihydropyrrolo[3,2-b]pyrroles are summarized. Many two- and three-step reaction sequences have been developed, and have allowed access to a broad variety of structures, including not only the parent 1,4-dihydropyrrolo[3,2-b]pyrroles, but also their π-expanded analogues. The newest approaches are critically compared with older strategies. The reactivity of these compounds is also reviewed, with special emphasis on electrophilic aromatic substitution. The synthesis of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 86 publications
0
32
0
Order By: Relevance
“…The hypothesis that NH-π interaction ensures conjugation of electrons in either direction and increases the charge mobility is an interesting proposition to explore further. 8,10 Even so, the prospect remained largely unexploited until 2013, owing to the lack of an effi cient synthesis strategy. A simple one-pot-domino reaction to synthesize DHPP`s with relatively moderate yields developed by Gryko et al 11 (Figure 1) were synthesized following reported protocols.…”
Section: Resultsmentioning
confidence: 99%
“…The hypothesis that NH-π interaction ensures conjugation of electrons in either direction and increases the charge mobility is an interesting proposition to explore further. 8,10 Even so, the prospect remained largely unexploited until 2013, owing to the lack of an effi cient synthesis strategy. A simple one-pot-domino reaction to synthesize DHPP`s with relatively moderate yields developed by Gryko et al 11 (Figure 1) were synthesized following reported protocols.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds have received increasing interest since Gryko and co‐workers developed a one‐pot synthetic process to access tetraaryl‐pyrrolo[3,2‐ b ]pyrroles in 2013 . PPs have high thermal and photo‐stability, high fluorescence quantum yields, good absorptivity and optical brightness . Along with thieno[3,2‐ b ]thiophenes, PPs are also attractive materials in current optoelectronics and in sensors…”
Section: Figurementioning
confidence: 99%
“…Our attention is focused on heteroacenes bearing a dihydropyrrolo[3,2‐ b ]pyrrole core. The pyrrolo[3,2‐ b ]pyrrole core is more electron‐rich than thieno[3,2‐ b ]thiophene, and the open valence on the N atom might be utilized to modify the solubility of the molecule for solution‐processable organic semiconductor . In the past several years, heteroacenes bearing a dihydropyrrolo[3,2‐ b ]pyrrole core have attracted an increasing attention as building blocks for organic light‐emitting diodes (OLEDs), organic solar cells (OSCs), and OFETs .…”
Section: Introductionmentioning
confidence: 99%
“…The pyrrolo [3,2-b] pyrrole core is more electron-rich than thieno [3,2-b]thiophene, and the open valence on the N atom might be utilized to modify the solubility of the molecule for solution-processable organic semiconductor. [5] In the past several years, heteroacenes bearing a dihydropyrrolo [3,2-b]pyrrole core have attracted an increasing attention as building blocks for organic light-emitting diodes (OLEDs), [6] organic solar cells (OSCs), [7] and OFETs. [8] For instance, Park et al [8b] synthesized a dihydropyrrolo [3,2-b]pyrrole based π-conjugated molecule with an exceptionally field-effect high hole mobility of 0.79 cm 2 V À 1 s À 1 .…”
Section: Introductionmentioning
confidence: 99%